Constitution-making and the Permanence of the Constitution - Szakály, Zsuzsa (Comparative Constitutionalism in Central Europe: Analysis on Certain Central and Eastern European Countries, 2022)
After the adoption of the first modern constitution – that of the United States – a dispute started over the possible permanence of the document. While some states hold minor interest in creating special rules for amending the constitution,1 other states created lengthy and circumstantial rules.2 The rules for adopting and amending the constitution can show the attitude and the level of respect towards the constitution itself. The aim of this chapter is to examine these processes and dynamics in the following states: Croatia, Czech Republic, Hungary, Poland, Romania, Serbia, Slovakia and Slovenia. I first examine the basic definitions and theories related to the dynamics at play in constitutional amendments and then the characteristics of the examined states’ constitutional attributes. The age of the constitution itself and the number of constitutional amendments can illustrate a few basic points related to the issue of constitution-making and constitutional amendment. While some of the analysed constitutions guard the amendment process with several strict rules, some others use only slightly different rules for constitutional amendment compared to ordinary legislation. I thus examine the textual and practical rigidity of the formal constitutional amendment rules. The significance of the adoption and the amendment of a constitution cannot be emphasised enough as the stability of the whole legal system is based on this document. After analysing the rules of the adoption and the amendment of the constitutions of Central and Eastern Europe, I draw several conclusions.KEYWORDS: constitution adoption, constitutional amendment, constitutional rigidity, constitutional flexibility, amendment frequency.